Multilocus sequence typing and genomic characterization of the novel Streptomyces strain SCPE-10, that resists 2,4-D toxicity and has bioremediation potential - Nildo Alfredo Nhampossa; João Victor Castro de Almeida Araújo; Vicente Almeida Serafim da Silva; João Ricardo Vidal Amaral; Cinara Souza da Conceição; Carlos Alberto Xavier Gonçalves; Eamim Daidrê Squizani; Sheila da Silva; Marcia Soares Vidal; Yinglong Chen; Andrew Macrae; Rodrigo Pires do Nascimento (Brazilian Journal of Microbiology, 2026)
The widespread use of aromatic herbicides such as 2,4-dichlorophenoxyacetic acid (2,4-D) has led to persistent environmental contamination, requiring efficient and sustainable biodegradation strategies. In this study, we isolated and characterized a novel actinobacterial strain, Streptomyces sp. SCPE-10, from contaminated coastal soil, capable of using 2,4-D as its sole carbon source. Phenotypic assays revealed robust growth on aromatic substrates, while whole-genome sequencing (Submission no. SUB15461668 ) followed by multilocus sequence analysis (16 S rRNA, recA, rpoB, atpD, gyrB, and trpB) revealed that SCPE-10 is closely related to Streptomyces phaeoluteichromatogenes . Functional genome annotation revealed a high abundance of genes involved in aromatic compound degradation, including cytochrome P450 monooxygenases, ring-cleaving dioxygenases, and dehalogenases. KEGG and antiSMASH analyses identified multiple metabolic pathways and 28 biosynthetic gene clusters (BGCs), including clusters for polyketides, nonribosomal peptides, terpenes, siderophores, and ectoine. Notably, SCPE-10 harbors key genes related to the degradation of benzoate, naphthalene, toluene, xylene, and 2,4-D, indicating broad-spectrum catabolic potential. These findings suggest that Streptomyces sp. SCPE-10 is a promising candidate for the bioremediation of herbicide-contaminated environments and the exploration of novel secondary metabolites.

Role of kaolinite epigenesis in ferruginous oolitic micronodule formation in Plinthosols from Central Brazil - Daniela Schievano de Campos; Thiago Tavares Vidoca; Raphael Rodrigues Brizzi; Hermes Dias Brito; Michele Ribeiro Ramos; Rodrigo Estevam Munhoz de Almeida; Pablo Vidal-Torrado (CATENA, 2026)

Hybrid magnetic GO·CNT·Fe3O4 nanomaterial for escitalopram removal: Synthesis, characterization, adsorption mechanisms, and biosafety assessment - Leonardo Vidal Zancanaro; Taíse Regina Schuster Montagner; Najla AlMasoud; Taghrid S. Alomar; Franciane Batista Nunes; Theodoro da Rosa Salles; Alana Torres Viero; Claudir Gabriel Kaufmmann Junior; Arthur Harres de Oliveira; Bernhard Westermann; Alencar Kolinski Machado; Sérgio Roberto Mortari; et al. (Journal of Environmental Chemical Engineering, 2026)

Lianas and trees 30-years after liana cutting and selective logging in the Amazon - Vitoria Duarte Derisso; Maria Tereza Grombone-Guaratini; Francis E. Putz; Rodrigo Costa Pinto; Iran Paz Pires; Edson Vidal (Forest Ecology and Management, 2026)

Primary infection with a Brazilian chikungunya virus isolate protects immunocompetent mice against detectable viremia following homologous rechallenge - Naiara Soares da Silva; Mayanna Moreira Costa Fogaça; Elmo José dos Santos; Bruna Santos Souza da Silva; Ruth Dálety da Silva Brito; Rodrigo Lucas Ferreira do Carmo; Amanda da Rocha Santos; Milena Silva Souza; Tarcisio Macedo Silva; Eric Roberto Guimarães Rocha Aguiar; Alexander Birbrair; Paloma Oliveira Vidal; et al. (Archives of Virology, 2026)
Chikungunya virus (CHIKV) is an arthropod-borne virus responsible for an acute febrile illness characterized by severe polyarthralgia, predominantly affecting peripheral joints. In a substantial proportion of patients, these symptoms may progress to chronic manifestations that significantly impair quality of life. Animal models are therefore critical for the development of effective therapeutic and preventive strategies, including antiviral agents and vaccines. In this context, the aim of this study was to establish an experimental model of CHIKV infection using immunocompetent C57BL/6 mice. Animals were infected with CHIKV and subsequently monitored for clinical signs, viremia, viral dissemination across tissues, total leukocyte counts, and susceptibility to reinfection. Results revealed no deaths among the animals during the experimental period, and infected animals exhibited significant viremia as well as detectable viral loads in the popliteal lymph node, femoral bone marrow, and muscle, demonstrating CHIKV capacity to disseminate and reach multiple target tissues. In addition, a global reduction in leukocyte counts was observed in infected mice. Notably, animals previously infected with CHIKV were resistant to reinfection, indicating the establishment of a protective immune response, as evidenced by the presence of neutralizing antibodies. In conclusion, the murine model established in this study recapitulates key features of CHIKV infection and provides a robust platform for investigating viral pathogenesis, as well as for evaluating novel antiviral strategies and vaccine candidates.

A framework for updating the regulation of isolated power systems in light of the energy transition imperative: The case of Chile - Cristiane Silva-Carvalho; Johanna Höhl; Carlos Olivos; Juan Carlos Osorio-Aravena; Rodrigo Palma-Behnke; Dasla Pando-Flores; Bernardo Severino; David Watts; Daniel Olivares; Alejandro Angulo; Joaquín Lazo; Humberto Vidal (Utilities Policy, 2026)

Microbial Solubilization of Struvite from Municipal Wastewater: Impact of Naganishia albida on Phosphorus Solubilization, Uptake, and Lettuce Plant Growth - Valentina Carrillo; Rodrigo Pérez; Felipe González; Christian Santander; Antonieta Ruiz; Eduardo Holzafpel; Pablo Cornejo; Gladys Vidal (Journal of Soil Science and Plant Nutrition, 2026)

AI-guided Aspergillus oryzae bioconversion of cucumber-peanut substrates produces an umami-rich, chicken-like flavor for plant-based meat alternatives - Rodrigo A. Contreras; Patricio Caripán; Nicole Ferrada; Macarena Cantero; Marisol Pizarro; Ana Batista-Gonzalez; Héctor Henríquez; Matthew Sujanto; Camila Covarrubias; Claudia Vidal; Carla Pino; Romina Ansaldo; et al. (Food Bioscience, 2026)

The recovery of forest structure 30 years after timber harvesting: a comparison of harvesting methods using field inventories and drone-based LiDAR data - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2026)

Resistance exercise training similarly improves work efficiency and measured submaximal oxygen consumption during the 6-min walk test in healthy postmenopausal women and breast cancer survivors - Macarena Artigas-Arias; Rodrigo Muñoz-Cofre; Nicolás Vidal-Seguel; Andrea Alegría-Molina; Jorge Sapunar; Rui Curi; Gabriel Nasri Marzuca-Nassr (European Journal of Applied Physiology, 2026)

Impact of different management practices on tree biomass and carbon dynamics 30 years after logging in eastern Amazon - Edson Vidal; Nathalia Sousa Braga; Daigard Ricardo Ortega Rodriguez; Vitoria Duarte Derisso; Rodrigo Costa Pinto; Jéssy Anni Vilhena Senado; Jonathan William Trautenmüller (Journal of Environmental Management, 2026)

Do persistent mineralogical and geochemical signatures in highly weathered Oxisols reflect variations in basaltic lithotypes? - Elida Marina Nogueira; Vander de Freitas Melo; Rodrigo Studart Correa; Pablo Vidal-Torrado; Nádia Mariane Mucha; Jaime Antonio Almeida; Daniel Hanke; Jairo Calderari Oliveira Junior (CATENA, 2026)

Natural regeneration responses of tree species at the end of the first timber harvesting cycle in the Eastern Amazon - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

CNT@NiFe2O4 nanocomposite for phenobarbital removal: adsorption study and characterization - Claudir Gabriel Kaufmann Junior; Rubia Young Sun Zampiva; Annelise koop Alves; Rafael Tronco; Marco Rossi; Carlos Perez Bergman; Leonardo Vidal Zancanaro; Sergio Roberto Mortari; Cristiano Rodrigo Bohn Rhoden (Environmental Science and Pollution Research, 2024)

Cassava (Manihot esculenta) Brazilian cultivars have different chemical compositions, present prebiotic potential, and beneficial effects on the colonic microbiota of celiac individuals - Ísis Meireles Mafaldo; Lais Matias Araújo; Lucélia Cabral; Carlos Eduardo Barão; Melline Fontes Noronha; Jesse Rodrigo Fink; Thatyane Mariano Rodrigues de Albuquerque; Marcos dos Santos Lima; Hubert Vidal; Tatiana Colombo Pimentel; Marciane Magnani (Food Research International, 2024)

Removal of selective serotonin reuptake inhibitor using magnetic graphene oxide derivatives: Adsorption study in low drug concentration using HPLC quantification, in vitro safety, and phytotoxicity - Franciane Batista Nunes; Franciele da Silva Bruckmann; Altevir Rossato Viana; Theodoro da Rosa Salles; Leonardo Vidal Zancanaro; Daniele Soares Basso Rhoden; Camila Franco; André Passaglia Schuch; Guilherme Luiz Dotto; Luis Felipe Oliveira Silva; Claudete Gindri Ramos; Cristiano Rodrigo Bohn Rhoden (Journal of Environmental Chemical Engineering, 2024)

Magnetic graphene derivates for efficient herbicide removal from aqueous solution through adsorption - Theodoro da Rosa Salles; Leonardo Vidal Zancanaro; Franciele da Silva Bruckmann; Wagner Jesus Garcia; Artur Harres de Oliveira; Luiza Baumann; Daniele Soares Basso Rhoden; Edson Irineu Muller; Diego Stefani Teodoro Martinez; Sergio Roberto Mortari; Cristiano Rodrigo Bohn Rhoden (Environmental Science and Pollution Research, 2024)

Phosphorus recovery from domestic wastewater: A review of the institutional framework - Valentina Carrillo; Rodrigo Castillo; Albert Magrí; Eduardo Holzapfel; Gladys Vidal (Journal of Environmental Management, 2024)

Lean-circular maturity model (LCMM) for companies' self-assessment in terms of process, product and life cycle thinking - Marina Hernandes de Paula e Silva; Ricardo Coser Mergulhão; José Geraldo Vidal Vieira; Andrea Brasco Pampanelli; Rodrigo Salvador; Diogo Aparecido Lopes Silva (Waste Management, 2024)

Combining geomechanical and hydrogeological modeling for drainage analysis in Block Caving mine development - Ramón Díaz; René Gómez; Rodrigo Vidal; Asieh Hekmat; Diego Oyarzo (International Journal of Rock Mechanics and Mining Sciences, 2024)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Magnitude of bycatch of Hippocampus patagonicus, an endangered species, in trawl fisheries in Southeast and South Brazil - Rosana Beatriz Silveira; Marcelo Derzi Vidal; José Rodrigo Santos Silva (Frontiers in Marine Science, 2023)
One of the biggest threats to the world’s fish stocks is trawling with indiscriminate capturing of non-target organisms, typically referred to as bycatch. Some species of seahorses are globally threatened and are often targets caught as bycatch. The aim of this work is to describe the magnitude of bycatch of the Patagonian seahorse Hippocampus patagonicus (Sygnathidae) in trawling fisheries in the Southeast and South Brazil. Between 2016 and 2018 we monitored the catch of five trawling vessels off the coast of Rio de Janeiro and Sao Paulo. A total of 2,041 individuals of H. patagonicus were captured, 1,183 males and 858 females. They were evaluated as for injuries suffered during dragging. The average rate of body damage was 33%. Based on the individuals captured and the analysis of on-board maps, an average CPUE of 3.36 with a standard deviation of 5.95/ind./day/vessel was estimated for the study area, extrapolating an incidental removal of 2,282,515 individuals per year, or 9,427 metric tons of seahorses, along the South and Southeast Brazil, where 3700 trawlers operate, an area recognized as the geographic distribution of H. patagonicus in Brazil

Calibration of a Three-dimensional Slope Stability Evaluation in Brazilian iron Open Pit Mine - Vidal Félix Navarro Torres; Rodrigo Dockendorff; Juan Manuel Girao Sotomayor; Cristian Castro; Aristotelina Ferreira da Silva (Geotechnical and Geological Engineering, 2023)

Residual oil saturation investigation in Barra Velha Formation reservoirs from the Santos Basin, Offshore Brazil: A sedimentological approach - Ronaldo Herlinger; Luiz Fernando De Ros; Rodrigo Surmas; Alexandre Vidal (Sedimentary Geology, 2023)

Unveiling the Role of Dynamic Alternative Splicing Modulation After Infestation with Sea Lice (Caligus rogercresseyi) in Atlantic Salmon - Scarleth Bravo; Francisco Leiva; Javier Moya; Osiel Guzman; Rodrigo Vidal (Marine Biotechnology, 2023)

Long-term carbon storage in Brazilian Cerrado soils – a conjunction of wildfires, bioturbation, and local edaphic controls on vegetation - Judith Schellekens; Marina Justi; Rodrigo Macedo; Márcia Regina Calegari; Peter Buurman; Thomas W. Kuyper; Plínio Barbosa de Camargo; Pablo Vidal-Torrado (Plant and Soil, 2023)

Evaluation of urban pollution in a tropical lacustrine ecosystem by using n-alkanes and sterols as biomarkers - Rodrigo de Lima Sobrinho; Gabriel da Costa Peçanha; Thallis Martins de Souza; Luiz Carlos Cotovicz Junior; Luciana Oliveira Vidal; Annibal Duarte Pereira Netto; Marcelo Corrêa Bernardes (Environmental Pollution, 2023)

Hydrofracturing in situ stress measurements of itabirite in the Brazilian Ferriferous Quadrangle and their limitations - Henrique de Andrade Penido; Rodrigo Peluci de Figueiredo; André Pacheco de Assis; Vidal Félix Navarro Torres; Juan Manuel Girao Sotomayor; Alessandro Guimarães (Geotechnical and Geological Engineering, 2022)

Rhizosphere Management for Phytoremediation of Copper Mine Tailings - Rodrigo Pérez; Yasna Tapia; Mónica Antilén; Manuel Casanova; Catalina Vidal; Sivagnanam Silambarasan; Pablo Cornejo (Journal of Soil Science and Plant Nutrition, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Temporal Gene Expression Signature of Plasma Extracellular Vesicles-MicroRNAs from Post-Smolt Coho Salmon Challenged with Piscirickettsia salmonis - Francisco Leiva; Scarlet Bravo; Killen Ko Garcia; Javier Moya; Osiel Guzman; Rodrigo Vidal (Marine Biotechnology, 2021)

Greenhouse gas emissions (CO2 and CH4) and inorganic carbon behavior in an urban highly polluted tropical coastal lagoon (SE, Brazil) - Luiz C. Cotovicz; Renato P. Ribeiro; Carolina Ramos Régis; Marcelo Bernardes; Rodrigo Sobrinho; Luciana Oliveira Vidal; Daniel Tremmel; Bastiaan A. Knoppers; Gwenaël Abril (Environmental Science and Pollution Research, 2021)

Targeting the Dopaminergic System in Autoimmunity - Pia M. Vidal; Rodrigo Pacheco (Journal of Neuroimmune Pharmacology, 2020)

De novo Assembly and Characterization of Patagonian Toothfish Transcriptome and Develop of EST-SSR Markers for Population Genetics - Jorge Touma; Killen Ko García; Scarleth Bravo; Francisco Leiva; Javier Moya; Luis Vargas-Chacoff; Alberto Reyes; Rodrigo Vidal (Frontiers in Marine Science, 2019)

Novel microsatellite markers discovery in Patagonian toothfish (Dissostichus eleginoides) using high-throughput sequencing - Killen Ko Garcia; Jorge Touma; Scarleth Bravo; Francisco Leiva; Luis Vargas-Chacoff; Ariel Valenzuela; Patricio Datagnan; Rodolfo Amthauer; Alberto Reyes; Rodrigo Vidal (Molecular Biology Reports, 2019)

Metal concentrations and source identification in Chilean public children’s playgrounds - Delia Rodríguez-Oroz; Rodrigo Vidal; Francisco Fernandoy; Fabrice Lambert; Felipe Quiero (Environmental Monitoring and Assessment, 2018)

De novo Assembly, Characterization and Functional Annotation of Southern Hake (Merluccius australis) Transcriptome - Daniela Reyes; John Gold; Ruth González; Rodrigo Vidal (Frontiers in Marine Science, 2016)

Uncertainty analysis in the environmental assessment of an integrated management system for restaurant and catering waste in Spain - Neus Escobar Lanzuela; Francisco Javier Ribal Sanchís; Alfredo Rodrigo Señer; Gabriela Clemente Polo; Andrés Pascual Vidal; Neus Sanjuán Pellicer (The International Journal of Life Cycle Assessment, 2015)

Modelling transport of chokka squid ( L oligo reynaudii ) paralarvae off S outh A frica: reviewing, testing and extending the ‘ W estward T ransport H ypothesis’ - Rodrigo S. Martins; Michael J. Roberts; Christophe Lett; Nicolette Chang; Coleen L. Moloney; Maurício G. Camargo; Erica A. G. Vidal (Fisheries Oceanography, 2014)
Annual landings of chokka squid ( L oligo reynaudii ), an important fishing resource for South Africa, fluctuate greatly, and are believed to be related to recruitment success. The ‘Westward Transport Hypothesis’ ( WTH ) attributes recruitment strength to variability in transport of newly hatched paralarvae from spawning grounds to the ‘cold ridge’ nursery region some 100–200 km to the west, where oceanographic conditions sustain high productivity. We used an individual‐based model ( IBM ) coupled with a 3‐D hydrodynamic model ( ROMS ) to test the WTH and assessed four factors that might influence successful transport – Release Area, Month, Specific Gravity (body density) and Diel Vertical Migration ( DVM ) – in numerical experiments that estimated successful transport of squid paralarvae to the cold ridge. A multifactor ANOVA was used to identify the primary determinants of transport success in the various experimental simulations. Among these, release area was found to be the most important, implying that adult spawning behaviour (i.e., birth site fidelity) may be more important than paralarval behaviour in determining paralarval transport variability. However, specific gravity and DVM were found to play a role by retaining paralarvae on the shelf and optimizing early transport, respectively. Upwelling events seem to facilitate transport by moving paralarvae higher in the water column and thus exposing them to faster surface currents.

Isolation and characterization of microsatellite markers in the southern hake, Merluccius australis - Mark A. Renshaw; David S. Portnoy; Rodrigo Vidal; John R. Gold (Conservation Genetics Resources, 2011)

Patterns of endemism in south‐eastern Pacific benthic polychaetes of the Chilean coast - Rodrigo A. Moreno; Cristián E. Hernández; Marcelo M. Rivadeneira; Marcela A. Vidal; Nicolás Rozbaczylo (Journal of Biogeography, 2006)
Aim In this study we evaluate patterns of endemism for benthic polychaete species along the southeastern Pacific coast of Chile. Our goals were (1) to describe latitudinal gradients of endemism and identify areas of high endemism, (2) to evaluate the effect of biogeographical limits on endemism patterns, and (3) to evaluate indirectly the role played by evolutionary dynamics on patterns of endemism. Location South‐eastern Pacific coast of Chile, ranging from Arica (18° S) to Cape Horn (56° S). Methods We used a list of 178 species of endemic, shallow benthic polychaetes to evaluate patterns of endemism. Parsimony analysis of endemicity (PAE) and the endemism index (EI) were used to evaluate hierarchical relationships of endemism between different latitudinal bands, and to identify areas with high degrees of endemism and differences in endemism. We evaluated the effect of biogeographical limits on endemic polychaete fauna by testing for the existence of geometric constraints (mid‐domain effect). The role of evolutionary dynamics on latitudinal patterns of endemism was evaluated with nestedness analysis (NA) using the temperature index. Results The PAE analysis indicated two large, separate areas of endemism: (1) the northern area between 18° S and 38° S, and (2) the southern area between 39° S and 56° S. The endemism index showed a maximum value (32 species) around 39°–41° S. Species‐richness curves of each 3° band of latitude showed a clear mid‐domain effect (69%), but the two maximum points of species richness at mid‐latitudes (36° S to 38° S and 39° S to 41° S) did not correspond to the mid‐domain peak in species richness, presenting a greater number of species than expected by the mid‐domain effect. The nestedness analysis showed that the number of genera reaches a maximum of 70 at mid‐latitudes (36°–41° S), decreasing towards both the northern and southern areas. The spatial distribution of the entire data set of endemic species showed a nested pattern ( T ° = 24.5°, P Main conclusions Our results strongly support the existence of a latitudinal gradient of endemism for benthic polychaete species along the Chilean coast. The shape of this gradient is clearly non‐linear, with a marked peak of endemism occurring at mid‐latitudes (36°–41° S, endemism hotspot), which also corresponds to a peak in species richness. Furthermore, this hotspot is the midpoint separating two distinct areas of endemism to the north and south. We suggest that the observed pattern of endemism for benthic polychaete taxa of the Chilean coast can be explained by a combination of geometric constraints and historical mechanisms, such as the processes that affected the Chilean coast during the Neogene (e.g. ENSO, oxygen minimum zone, glaciations).

Microsatellites of Laminaria digitata tested in Lessonia nigrescens: Evaluation and improvement of cross amplification between kelps of two different families - Enrique A. Martínez; Leyla Cárdenas; Cecilia Figueroa; Rodrigo U. Vidal; Claire Billot (Journal of Applied Phycology, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Enhanced DNA extraction and PCR amplification of SSU ribosomal genes from crustose coralline algae - Rodrigo Vidal; Isabel Meneses; Macarena Smith (Journal of Applied Phycology, 2002)